SURGICAL CHEKLIST SEBAGAI UPAYA MENINGKATKAN PATIENT SAFETY - Irmawati, Nurisda Eva; Anggorowati, Anggorowati (JHeS (Journal of Health Studies), 2017)
Abstract: The purpose of this research is to study Literature review to determine whether the Surgical Safety Checklist can improve patient safety in the hospital in collaboration with other health team. This research method is the publication of the article searches on Google Scholar, PubMed, Ebscho with selected keywords ie Surgical Safety Checkliat, collaboration, Patient Safety. The search was performed by limiting the issue of 2006-2015. Results of literature search showed that the IPE can effectively build the ability of nurses to collaborate with other health professionals. IPE expected implementation can be implemented on an ongoing basis with the preparation over the maximum again, considering the health institution is a major provider of professional health personnel candidates.Keywords: surgical safety checklist, collaboration, patient safety